Rancang Bangun Sistem Penerimaan Peserta Didik Baru Berbasis Web (Studi Kasus : SDN Lemahduhur) - Rapael Hutasoit; Fendi Indra Pradana; Muhammad Mabdail Hidayat; Wasis Haryono (CV. Multi Kreasi Media, 2025)
SD Negeri Lemahduhur is a public elementary school that conducts new student admissions (PPDB) every year. Until now, the PPDB process has been carried out manually, requiring prospective students or their parents to visit the school in person to collect forms, fill in data, and submit physical documents. This process is considered inefficient as it takes time, incurs costs, and is prone to input errors and data loss. Because of these problems, the study's main goal is to create a web- based PPDB system that makes registering easier and increases the accuracy and speed of administrative work. Observation, conversation, and record study are some of the research methods that are used. The system was created using the Waterfall method of software development, and it was tried using the Black Box method to make sure that all of its functions work the way users want them to. The language used is PHP, and the database is MySQL.The planned online PPDB system has several main features, such as the ability to register online, share necessary papers, make payments through a bank transfer, and get alerts about the results of the selection. The method works well and meets the school's goals for a more current, open, and effective PPDB process, as shown by the test results.